Analisis Istinbât? Hukum Akad Perkawinan melalui Media Elektronik dalam Perspektif Hukum Islam - A. Fauzi Aziz (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2017)
Marriage is seen as a form worship which very sacred, at the present time, it has been the practice of marriages that use the facilities telephone or Cybernet, and also with the technology one step ahead, namely video teleconference. Where one party at a time doing this marriage ceremony, he was somewhere else that causes the marriage contract becomes ittih?âd al-majlis (merging chamber). With using a qualitative approach with Reserch Library obtained two different interpretations related to the ittih?âd al-majlis. The H?anafîyah interpret it ijâb-qabûl to be done within the time contained in the marriage ceremony, not be done in two separate intervals. So, when guided by the interpretation of this argument, marriage ceremony via electronic media can be understood validity. The Shâfi?îyah stated that the united chamber required, to maintain continuity between ijâb and qabûl, at once must embody fulfillment of tasks of two witnesses. Because according to this argument, the two witnesses should be capable see with his eyes that ijâb and qabûl it was actually spoken by two actors contract. So when referring to the second opinion, the practice of marriage ceremony via electronic media is not valid.